Krisis Kepercayaan; Refleksi Filsafat Manusia terhadap Kerentanan Emosional dan Penyebaran Hoaks dalam Era Digital - Gobang, Paulus Wilfridus; Janson Seran, Kuniberth De Forbin; Berun, Dominggus; Satyawardana, Dimas (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In the modern era filled with rapid advances in technology and information, the hoax phenomenon has become a very worrying global issue. Hoaxes, or false information, are often spread quickly and widely via social media and digital platforms, exploiting people's emotional vulnerabilities. The aim of this research is to understand the hoax phenomenon and its impact on human emotions in the current digital context. This research method uses a literature analysis approach using a multidisciplinary approach, namely combining theories from psychology, sociology and philosophy to provide a comprehensive understanding of the relationship between hoaxes and human emotions in the context of human philosophy. The literature review used is the most updated journals related to the topic discussed. The results of this research define hoaxes as false or misleading information that is spread with the aim of deceiving the recipient of the information. Hoaxes are often manipulated to trigger strong emotional responses, such as fear, anger, or confusion, which makes individuals more susceptible to misleading information.In the perspective of human philosophy, emotions are seen as a fundamental aspect of human experience that influences the way we understand and respond to the world around us.  A deeper understanding of the fragility of human emotions can help develop more effective strategies to combat the spread of hoaxes and strengthen people's emotional resilience in this digital era.